Iterative Ordered Statistics Decoding of Product Codes - Shen, Yifei; Ren, Yuqing; Burg, Andreas (2023 12th International Symposium on Topics in Coding (ISTC), 2023)
Product codes have emerged as a key technique in optical communications. However, the conventional ChasePyndiah decoding algorithm faces challenges in achieving the high throughput required by future optical transport networks. Consequently, research efforts have focused on optimizing hard decision decoding algorithms, such as iterative bounded distance decoding (iBDD). In this paper, we propose an iterative ordered statistics decoding (iOSD) algorithm that adopts OSD to decode component codes based on fixed soft messages. We introduce the bounded OSD technique and integrate additional iBDD iterations to mitigate error propagation and correct residual errors. Simulation results show that the proposed iOSD can achieve the error-correction performance of Chase-Pyndiah decoding.